Flagellin Immunization against Urinary Tract Infection Caused by p. Mirabilis - Astabraq A. Al-Sodanii (Journal of Global Pharma Technology, 2016)
Objective Proteus mirabilis is dimorphic a (gram negative bacteria that alternates between a rod –shaped swimmer stage and multinucleate, highly elongated swarming stage. Methods Urine Samples collected from three hospitals in Baghdad city from adult and child patients Suffering from urinary tract infections for 6 months .The samples get reached 1152 distributed among the patients old between few days to 80 years most patients living in hospital with urinary tract catheter , 56 samples of Proteus mirabilis were identified after isolation and diagnosis of bacterial species in different methods because there different complications in UTIs Patients specially Stone formation , catheter obstruction , and renal damage. Results these bacteria were diagnosis in api 20 E and vitek2 system and one isolate of Proteus mirabilis was selected for the study according to distance movement by measurement (swarming motility). Flagellin which is the flagella protein was extracted and predicated, followed by SDS-polyacrylamide gel electrophoresis for protein molecular weight estimation and concentration of protein counted by Bradford method ,then immunization protocol were tested in Albino rabbits in different concentrations 10,20,40 microgram from flagella protein then immunoglobulin antibody IgG ,IgM in serum were tested by single radial immunoglobulin diffusion plate , positive results showed raised the concentrations of these antibodies with high significant differences .Immunized females rabbits was tested to ascending urinary tract infection challenge by inoculation 145Ã—107